Pengaruh Gaya Kepemimpinan Transforsmasional Dan Budaya Organisasi Terhadap Kinerja Guru Smk Swasta Di Kecamatan Pesanggarahan Jakarta Selatan - Riswanto Riswanto; Joned Ceilandra Saksana; Mada Komala (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
This study aims to analyze the direct and indirect influence of Transformational Leadership Style and Organizational Culture on the Performance of Private Vocational School Teachers in Pesanggrahan District, South Jakarta. The hypotheses tested include: (1) Transformational Leadership Style has a significant direct influence on Teacher Performance, (2) Organizational Culture has a significant direct influence on Teacher Performance, (3) Transformational Leadership Style has a significant direct influence on Organizational Culture in Private Vocational Schools, and (4) Transformational Leadership Style has a significant indirect influence on Teacher Performance through Organizational Culture. This study uses a quantitative method with a population of 14 private vocational schools and a sample of 220 teachers in Pesanggrahan District. The sampling technique uses proportional random sampling, with primary data obtained through questionnaires. To test the hypothesis, a statistical test with Path Analysis was used. The results show that: (1) Transformational Leadership Style has a significant direct influence on Organizational Culture (Sig = 0.000 < 0.05), (2) Transformational Leadership Style and Organizational Culture have a significant direct influence on Teacher Performance (Sig = 0.000 < 0.05), (3) Organizational Culture has a significant direct influence on Teacher Performance (Sig = 0.000 < 0.05), and (4) Transformational Leadership Style has an indirect influence significant on Teacher Performance through Organizational Culture at Private Vocational Schools in Pesanggrahan District, South Jakarta.